A composite material for 3D printing and preparation method thereof
By using specific formula composite materials in 3D printed materials, the problems of insufficient mechanical properties, poor heat resistance, flammability and hydrolysis degradation of polylactic acid materials are solved, and the comprehensive performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202410754015.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Polylactic acid has problems such as insufficient mechanical properties, poor heat resistance, flammability and hydrolysis degradation in 3D printed materials, which limits its application scope.
Using a composite material formulation, including polylactic acid resin, poly(4-hydroxybutyrate), compatibilizers, fillers, anti-hydrolyzers, antioxidants, plasticizers and nucleating agents, through specific mixing and extrusion The process is used to prepare composite materials for 3D printing.
The mechanical properties, heat resistance, flame retardant properties and hydrolysis resistance of 3D printed composite materials have been significantly improved, and the scope of application has been expanded.
Smart Images

Figure BDA0004888922890000171
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing materials, and in particular to a composite material for 3D printing and a preparation method thereof. Background Art
[0002] Polylactic acid has been widely studied due to its non-toxic, biocompatible, biodegradable, and plastic molding properties, and is widely used in biomedicine, packaging coatings, 3D printing and other fields. However, in the actual application of polylactic acid in 3D printing materials, it has disadvantages such as low strength and poor heat resistance, which limits its scope of application. The flame retardant properties of ordinary polylactic acid are only the lowest level of the material's combustion performance, and it is extremely flammable, which is not conducive to the use of polylactic acid materials in occasions where high flame retardant properties are required. The polylactic acid molecular chain contains a polyester structure. Under the action of acid or alkali, the ester group will hydrolyze, resulting in hydrolysis and degradation of the material, which has an adverse effect on the mechanical properties of the material.
[0003] In summary, it is necessary to develop appropriate modification methods to solve the problems of insufficient mechanical properties, poor heat resistance, flammability and hydrolysis degradation of polylactic acid materials during actual use, so as to improve the comprehensive performance of polylactic acid materials. Summary of the invention
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A composite material for 3D printing, comprising the following raw materials in parts by weight: 60-70 parts of polylactic acid resin, 30-40 parts of poly(4-hydroxybutyrate) (see the paper "Study on Toughening and Modifying Polylactic Acid and 3D Printing Performance Using Bio-based Degradable Poly(4-hydroxybutyrate)"), 6-8 parts of a compatibilizer, 8-12 parts of a filler, 1.2-1.5 parts of an anti-hydrolysis agent, 0.6-0.8 parts of an antioxidant, 1-3 parts of a plasticizer, and 1-3 parts of a nucleating agent;
[0006] The filler is prepared by mixing nano silicon dioxide and nano antimony trioxide in a mass ratio of 2:1;
[0007] The antioxidant is prepared by mixing antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0008] The plasticizer is acetyl tributyl citrate;
[0009] The nucleating agent is polylactic acid nucleating agent TMC-328;
[0010] The preparation of the composite material for 3D printing comprises the following steps:
[0011] Polylactic acid resin, poly (4-hydroxybutyrate), compatibilizer, filler, anti-hydrolysis agent, antioxidant, plasticizer and nucleating agent are added to a reactor and stirred for 5-10 minutes, and then transferred to a twin-screw extruder to extrude material strips at 180-210° C. and granulate to obtain a composite material for 3D printing.
[0012] The preparation of the compatibilizer comprises the following steps:
[0013] Step A1: 4-nitroamphetamine, potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then methacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b. The mixed solution b is slowly added dropwise into the mixed solution a in an ice-water bath at 0° C. After the addition is completed, the temperature is raised to 40° C. and the mixture is stirred at a constant temperature for 10 hours to obtain a reaction product 1;
[0014] Further, the dosage ratio of 4-nitroamphetamine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 45-55 mL; the dosage ratio of methacryloyl chloride and dimethyl sulfoxide is 0.1 mol: 25-35 mL; the dosage ratio of mixed solution a and mixed solution b is 50-60 mL: 30-40 mL;
[0015] During the reaction of step A1, the amino group of 4-nitroamphetamine reacts with methacryloyl chloride to generate a nitro-containing reaction product 1;
[0016] Step A2: Add toluene, hydrogenated silicone oil, hydroquinone, and cis-dichlorobis(pyridyl)platinum into a flask, stir and introduce nitrogen protection, slowly add reaction product 1, slowly raise the temperature to 70-80° C., stir and react for 3-4 hours, and vacuum to remove the solvent to obtain reaction product 2;
[0017] Further, the amount ratio of the reaction product 1, toluene, hydrogen-containing silicone oil, hydroquinone and cis-dichlorobis(pyridyl)platinum is 1-1.5 mol: 100-110 ml: 1 mol: 0.5 mol: 0.015-0.020 mol;
[0018] During the reaction of step A2, the hydrogen-containing silicone oil reacts with the reaction product 1 under the catalysis of cis-dichlorobis(pyridyl)platinum, and the Si-H bond and the C=C bond are added to generate the reaction product 2 containing the polysiloxane chain;
[0019] Step A3: Add the reaction product 2 and toluene into a three-necked flask, heat to 45-55° C., start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5 hours to obtain an aromatic primary amine product; add glycidyl methacrylate, the aromatic primary amine product, toluene and tetrabutylammonium bromide into the flask, start stirring, and stir and react at 40-50° C. for 3 hours to obtain a reaction product 3;
[0020] Further, the amount ratio of the reaction product 2, toluene and sodium dithionite is 0.1 mol: 115-125 mL: 0.1-0.15 mol; the amount ratio of glycidyl methacrylate, aromatic primary amine product, toluene and tetrabutylammonium bromide is 0.35-0.40 mol: 0.1 mol: 360-380 mL: 0.025-0.030 mol;
[0021] During the reaction of step A3, the nitro group on the benzene ring of the reaction product 2 is reduced to an amino group, i.e., an aromatic primary amine product is obtained; the epoxy group of glycidyl methacrylate then opens the ring with the amino group of the aromatic primary amine product to obtain a hydroxyl-containing reaction product 3;
[0022] Step A4: epichlorohydrin and the reaction product 3 are added to methanol, trimethylamine is added under stirring, and the mixture is refluxed and stirred at 70-80° C. for 3-4 hours to obtain a ring-opening product; the ring-opening product is then added to a sodium hydroxide solution, and stirred at room temperature for 5 hours, and extracted and distilled to obtain a reaction product 4;
[0023] Furthermore, the dosage ratio of epichlorohydrin, reaction product 3, methanol, and trimethylamine is 0.2 mol: 0.1 mol: 160-170 mL: 0.01-0.015 mol; the dosage ratio of the ring-opening product and the sodium hydroxide solution is 3-4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%;
[0024] During the reaction of step A4, the hydroxyl group of the reaction product 3 is ring-opened with epichlorohydrin to obtain a ring-opened product; the ring-opened product is ring-closed in a sodium hydroxide solution to obtain a reaction product 4 containing an epoxy group;
[0025] Step A5: first add poly (4-hydroxybutyrate) to an internal mixer and stir at 60 r / min for 3 min, then add di (tert-butyldioxyisopropyl) benzene, continue stirring for 10-20 min, then add reaction product 4 and stir for 10-20 min, heat to 155-165° C., mix and stir for 10-15 min, and dry in an oven at 45° C. to obtain a compatibilizer;
[0026] Further, the amount ratio of poly(4-hydroxybutyrate), di(tert-butyldioxyisopropyl)benzene and reaction product 4 is 10 g:0.1 g:1 g;
[0027] During the reaction of step A5, the reaction product 4 is grafted with poly(4-hydroxybutyrate) by melt grafting to obtain a compatibilizer;
[0028] The preparation of the anti-hydrolysis agent comprises the following steps:
[0029] Step B1: add bis(4-nitrobenzyl)chlorophosphate to toluene, then add ethyl 2-methyl-3-(methylamino)propionate, stir at 0-5°C for 2h, then heat to 40-50°C, reflux at constant temperature and stir for 1h, filter, extract and dry to obtain reaction product a;
[0030] Further, the usage ratio of bis(4-nitrobenzyl)chlorophosphate, toluene, and ethyl 2-methyl-3-(methylamino)propionate is 0.1 mol:80-90 mL:0.1 mol;
[0031] During the reaction of step B1, phosphoryl chloride in bis(4-nitrobenzyl) chlorophosphate reacts with the secondary amino group of ethyl 2-methyl-3-(methylamino)propionate to generate a reaction product a containing phosphoramide;
[0032] Step B2: Add the reaction product a and ethyl acetate into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product b;
[0033] Further, the usage ratio of the reaction product a, ethyl acetate, and sodium dithionite is 0.1 mol: 100-110 mL: 0.2-0.25 mol;
[0034] During the reaction of step B2, the nitro group of the reaction product a is reduced to an amino group to obtain a reaction product b containing a dibasic aromatic primary amine;
[0035] Step B3: Add xylene to a four-necked flask, introduce nitrogen, add the reaction product b and triphosgene at 75°C, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain a diisocyanate product; add the diisocyanate product to the flask, then add 3-methyl-1-phenyl-2-phosphopentene-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent;
[0036] Further, the usage ratio of xylene, reaction product b and triphosgene is 100mL: 0.1mol: 0.1mol; the usage ratio of diisocyanate product and 3-methyl-1-phenyl-2-phosphopentene-1-oxide is 0.1mol: 0.0020-0.0025mol;
[0037] During the reaction of step B3, the amino group of the reaction product b reacts with triphosgene to generate chloroamide, which is then heated to dehydrochlorinate to generate a diisocyanate product; the diisocyanate product is catalytically decarbonated to generate an anti-hydrolysis agent.
[0038] Beneficial effects of the present invention: The present invention discloses a composite material for 3D printing, including raw materials such as polylactic acid resin, poly(4-hydroxybutyrate), a compatibilizer, a filler, an anti-hydrolysis agent, an antioxidant, a plasticizer and a nucleating agent. The synthesized compatibilizer contains a poly(4-hydroxybutyrate) structure, an epoxy group and a polysiloxane chain; the poly(4-hydroxybutyrate) structure is similar to and compatible with the poly(4-hydroxybutyrate) in the raw material, and the poly(4-hydroxybutyrate) has high strength, good mechanical properties and excellent biodegradability, and the epoxy group and the end carboxyl group of the polylactic acid ring-opening reaction connect the compatibilizer with the molecular chain of the polylactic acid, thereby increasing the compatibility of the polylactic acid and the poly(4-hydroxybutyrate) in the raw material, thereby increasing the mechanical properties of the 3D printing composite material and making the material have a strong ability to resist deformation; the bond energy of the silicon-oxygen bond and the silicon-carbon bond contained in the polysiloxane chain is large, and a high energy is required for breaking, thereby improving the thermal stability of the compatibilizer molecule, thereby improving the heat resistance of the material.
[0039] The synthesized anti-hydrolysis agent contains polyester structure, polyphosphoramide structure and polymeric carbodiimide structure in its molecule; the polyester structure is similar to the main chain structure of polylactic acid, so that the compatibility and dispersibility of the anti-hydrolysis agent in the matrix are increased; the non-flammable gas generated by polyphosphoramide when the matrix burns forms a phosphorus-carbon foam insulation layer with the pyrophosphate protective film on the surface of the matrix, which can prevent the material from further burning, and has the synergistic flame retardant effect of phosphorus and nitrogen, so that the material has good flame retardant performance; the polymeric carbodiimide has an increased relative molecular weight and has the advantages of higher thermal stability and reduced usage compared with monomeric carbodiimide, so that the anti-hydrolysis agent can play a role stably and improve the anti-hydrolysis performance of the material. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A compatibilizer, the preparation of which comprises the following steps:
[0043] Step A1: 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then methacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is slowly added dropwise into the mixed solution a in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C and stirred at a constant temperature for 10 hours to obtain a reaction product 1; the amount ratio of 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 45 mL; the amount ratio of methacryloyl chloride and dimethyl sulfoxide is 0.1 mol: 25 mL; the amount ratio of the mixed solution a to the mixed solution b is 50 mL: 30 mL;
[0044] Step A2: toluene, hydrogen-containing silicone oil, hydroquinone, and cis-dichlorobis(pyridyl)platinum are added to a flask, stirred and nitrogen is introduced for protection, reaction product 1 is slowly added, the temperature is slowly raised to 70° C., stirred for reaction for 3 hours, and the solvent is removed by vacuum to obtain reaction product 2; the amount ratio of reaction product 1, toluene, hydrogen-containing silicone oil, hydroquinone and cis-dichlorobis(pyridyl)platinum is 1 mol: 100 ml: 1 mol: 0.5 mol: 0.015 mol;
[0045] Step A3: Add the reaction product 2 and toluene into a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain an aromatic primary amine product; add glycidyl methacrylate, the aromatic primary amine product, toluene and tetrabutylammonium bromide into a flask, start stirring, and stir and react at 40°C for 3 hours to obtain a reaction product 3; the amount ratio of the reaction product 2, toluene and sodium dithionite is 0.1 mol: 115 mL: 0.1 mol; the amount ratio of glycidyl methacrylate, the aromatic primary amine product, toluene and tetrabutylammonium bromide is 0.35 mol: 0.1 mol: 360 mL: 0.025 mol;
[0046] Step A4: Add epichlorohydrin and reaction product 3 to methanol, add trimethylamine under stirring, and react under reflux stirring at 70° C. for 3 hours to obtain a ring-opening product; then add the ring-opening product to a sodium hydroxide solution, and stir at room temperature for 5 hours, extract and distill to obtain a reaction product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol, and trimethylamine is 0.2 mol: 0.1 mol: 160 mL: 0.01 mol; the amount ratio of the ring-opening product and the sodium hydroxide solution is 3 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%;
[0047] Step A5: first add poly (4-hydroxybutyrate) to an internal mixer and stir at 60r / min for 3min, then add di (tert-butyldioxyisopropyl) benzene, continue stirring for 10min, then add the reaction product 4 and stir for 10min, then heat to 155°C, mix and stir for 10min, and dry in an oven at 45°C to obtain a compatibilizer; the amount ratio of poly (4-hydroxybutyrate), di (tert-butyldioxyisopropyl) benzene and reaction product 4 is 10g:0.1g:1g.
[0048] Example 2
[0049] A compatibilizer, the preparation of which comprises the following steps:
[0050] Step A1: 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then methacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is slowly added dropwise into the mixed solution a in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C and stirred at a constant temperature for 10 hours to obtain a reaction product 1; the amount ratio of 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 50 mL; the amount ratio of methacryloyl chloride and dimethyl sulfoxide is 0.1 mol: 30 mL; the amount ratio of the mixed solution a to the mixed solution b is 55 mL: 35 mL;
[0051] Step A2: toluene, hydrogen-containing silicone oil, hydroquinone, and cis-dichlorobis(pyridyl)platinum are added to a flask, stirred and nitrogen is introduced for protection, reaction product 1 is slowly added, the temperature is slowly raised to 75° C., stirred for reaction for 3.5 hours, and the solvent is removed by vacuum to obtain reaction product 2; the amount ratio of reaction product 1, toluene, hydrogen-containing silicone oil, hydroquinone and cis-dichlorobis(pyridyl)platinum is 1.2 mol: 105 ml: 1 mol: 0.5 mol: 0.017 mol;
[0052] Step A3: Add the reaction product 2 and toluene into a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring for reaction for 1.2 hours to obtain an aromatic primary amine product; add glycidyl methacrylate, an aromatic primary amine product, toluene and tetrabutylammonium bromide into a flask, start stirring, and stir and react at 45°C for 3 hours to obtain a reaction product 3; the amount ratio of the reaction product 2, toluene and sodium dithionite is 0.1 mol: 120 mL: 0.12 mol; the amount ratio of glycidyl methacrylate, an aromatic primary amine product, toluene and tetrabutylammonium bromide is 0.37 mol: 0.1 mol: 370 mL: 0.027 mol;
[0053] Step A4: Add epichlorohydrin and reaction product 3 to methanol, add trimethylamine under stirring, and react under reflux stirring at 75° C. for 3.5 hours to obtain a ring-opened product; then add the ring-opened product to a sodium hydroxide solution, stir at room temperature for 5 hours, extract and distill to obtain a reaction product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 165 mL: 0.012 mol; the amount ratio of the ring-opened product and the sodium hydroxide solution is 3.5 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%;
[0054] Step A5: first add poly (4-hydroxybutyrate) to an internal mixer and stir at 60r / min for 3min, then add di (tert-butyldioxyisopropyl) benzene, continue stirring for 15min, then add the reaction product 4 and stir for 15min, then heat to 160°C, mix and stir for 12min, and dry in an oven at 45°C to obtain a compatibilizer; the amount ratio of poly (4-hydroxybutyrate), di (tert-butyldioxyisopropyl) benzene and reaction product 4 is 10g:0.1g:1g.
[0055] Example 3
[0056] A compatibilizer, the preparation of which comprises the following steps:
[0057] Step A1: 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then methacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is slowly added dropwise into the mixed solution a in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C and stirred at a constant temperature for 10 hours to obtain a reaction product 1; the amount ratio of 4-nitrobenzenephetamine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 55 mL; the amount ratio of methacryloyl chloride and dimethyl sulfoxide is 0.1 mol: 35 mL; the amount ratio of the mixed solution a to the mixed solution b is 60 mL: 40 mL;
[0058] Step A2: toluene, hydrogen-containing silicone oil, hydroquinone, and cis-dichlorobis(pyridyl)platinum are added to a flask, stirred and nitrogen is introduced for protection, reaction product 1 is slowly added, the temperature is slowly raised to 80° C., stirred for reaction for 4 hours, and the solvent is removed by vacuum to obtain reaction product 2; the amount ratio of reaction product 1, toluene, hydrogen-containing silicone oil, hydroquinone and cis-dichlorobis(pyridyl)platinum is 1.5 mol: 110 ml: 1 mol: 0.5 mol: 0.020 mol;
[0059] Step A3: Add the reaction product 2 and toluene into a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.5 hours to obtain an aromatic primary amine product; add glycidyl methacrylate, an aromatic primary amine product, toluene and tetrabutylammonium bromide into a flask, start stirring, and stir and react at 50°C for 3 hours to obtain a reaction product 3; the amount ratio of the reaction product 2, toluene and sodium dithionite is 0.1 mol: 125 mL: 0.15 mol; the amount ratio of glycidyl methacrylate, an aromatic primary amine product, toluene and tetrabutylammonium bromide is 0.40 mol: 0.1 mol: 380 mL: 0.030 mol;
[0060] Step A4: epichlorohydrin and reaction product 3 are added to methanol, trimethylamine is added under stirring, and the mixture is refluxed and stirred at 80° C. for 4 h to obtain a ring-opened product; the ring-opened product is then added to a sodium hydroxide solution, and stirred at room temperature for 5 h, extracted and distilled to obtain a reaction product 4; the amount ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 170 mL: 0.015 mol; the amount ratio of the ring-opened product and the sodium hydroxide solution is 4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%;
[0061] Step A5: first add poly (4-hydroxybutyrate) to an internal mixer and stir at 60r / min for 3min, then add di (tert-butyldioxyisopropyl) benzene, continue stirring for 20min, then add the reaction product 4 and stir for 20min, then heat to 165°C, mix and stir for 15min, and dry in an oven at 45°C to obtain a compatibilizer; the amount ratio of poly (4-hydroxybutyrate), di (tert-butyldioxyisopropyl) benzene and reaction product 4 is 10g:0.1g:1g.
[0062] Example 4
[0063] An anti-hydrolysis agent, the preparation of which comprises the following steps:
[0064] Step B1: add bis(4-nitrobenzyl) chlorophosphate to toluene, then add ethyl 2-methyl-3-(methylamino)propionate, stir at 0°C for 2h, then heat to 40°C, reflux at constant temperature and stir for 1h, filter, extract and dry to obtain reaction product a; the amount ratio of bis(4-nitrobenzyl) chlorophosphate, toluene and ethyl 2-methyl-3-(methylamino)propionate is 0.1mol:80mL:0.1mol;
[0065] Step B2: Add the reaction product a and ethyl acetate into a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain the reaction product b; the amount ratio of the reaction product a, ethyl acetate, and sodium dithionite is 0.1 mol: 100 mL: 0.2 mol;
[0066] Step B3: Add xylene to a four-necked flask, introduce nitrogen, add the reaction product b and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain a diisocyanate product; add the diisocyanate product to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, reaction product b and triphosgene is 100mL:0.1mol:0.1mol; the amount ratio of diisocyanate product and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0020mol.
[0067] Example 5
[0068] An anti-hydrolysis agent, the preparation of which comprises the following steps:
[0069] Step B1: add bis(4-nitrobenzyl) chlorophosphate to toluene, then add ethyl 2-methyl-3-(methylamino)propionate, stir at 0°C for 2h, then heat to 45°C, reflux at constant temperature and stir for 1h, filter, extract and dry to obtain reaction product a; the amount ratio of bis(4-nitrobenzyl) chlorophosphate, toluene and ethyl 2-methyl-3-(methylamino)propionate is 0.1mol:85mL:0.1mol;
[0070] Step B2: Add the reaction product a and ethyl acetate into a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.2h to obtain the reaction product b; the amount ratio of the reaction product a, ethyl acetate and sodium dithionite is 0.1mol:105mL:0.22mol;
[0071] Step B3: Add xylene to a four-necked flask, introduce nitrogen, add the reaction product b and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain a diisocyanate product; add the diisocyanate product to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, reaction product b and triphosgene is 100mL:0.1mol:0.1mol; the amount ratio of diisocyanate product and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0022mol.
[0072] Example 6
[0073] An anti-hydrolysis agent, the preparation of which comprises the following steps:
[0074] Step B1: add bis(4-nitrobenzyl) chlorophosphate to toluene, then add ethyl 2-methyl-3-(methylamino) propionate, stir at 5°C for 2h, then heat to 50°C, reflux and react at constant temperature for 1h, filter, extract and dry to obtain reaction product a; the amount ratio of bis(4-nitrobenzyl) chlorophosphate, toluene and ethyl 2-methyl-3-(methylamino) propionate is 0.1mol:90mL:0.1mol;
[0075] Step B2: Add the reaction product a and ethyl acetate into a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1.5h to obtain the reaction product b; the amount ratio of the reaction product a, ethyl acetate and sodium dithionite is 0.1mol:110mL:0.25mol;
[0076] Step B3: Add xylene to a four-necked flask, introduce nitrogen, add the reaction product b and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain a diisocyanate product; add the diisocyanate product to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, reaction product b and triphosgene is 100mL:0.1mol:0.1mol; the amount ratio of diisocyanate product and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0025mol.
[0077] Example 7
[0078] A composite material for 3D printing, comprising the following raw materials in parts by weight: 60 parts of polylactic acid resin, 30 parts of poly(4-hydroxybutyrate) (see the paper "Study on Toughening and Modifying Polylactic Acid and 3D Printing Performance Using Bio-based Degradable Poly(4-hydroxybutyrate)"), 6 parts of a compatibilizer, 8 parts of a filler, 1.2 parts of an anti-hydrolysis agent, 0.6 parts of an antioxidant, 1 part of a plasticizer, and 1 part of a nucleating agent;
[0079] The filler is a mixture of nano silicon dioxide and nano antimony trioxide in a mass ratio of 2:1; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the plasticizer is acetyl tributyl citrate; and the nucleating agent is polylactic acid nucleating agent TMC-328;
[0080] The preparation of the composite material for 3D printing comprises the following steps:
[0081] Polylactic acid resin, poly (4-hydroxybutyrate), the compatibilizer obtained in Example 1, the filler, the anti-hydrolysis agent obtained in Example 4, the antioxidant, the plasticizer and the nucleating agent were added to a reaction kettle and stirred for 5 minutes, and then transferred to a twin-screw extruder to extrude material strips at 180° C. and granulated to obtain a composite material for 3D printing.
[0082] Example 8
[0083] A composite material for 3D printing, comprising the following raw materials in parts by weight: 65 parts of polylactic acid resin, 35 parts of poly(4-hydroxybutyrate) (see the paper "Study on Toughening and Modifying Polylactic Acid and 3D Printing Performance Using Bio-based Degradable Poly(4-hydroxybutyrate)"), 7 parts of a compatibilizer, 10 parts of a filler, 1.3 parts of an anti-hydrolysis agent, 0.7 parts of an antioxidant, 2 parts of a plasticizer, and 2 parts of a nucleating agent;
[0084] The filler is a mixture of nano silicon dioxide and nano antimony trioxide in a mass ratio of 2:1; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the plasticizer is acetyl tributyl citrate; and the nucleating agent is polylactic acid nucleating agent TMC-328;
[0085] The preparation of the composite material for 3D printing comprises the following steps:
[0086] Polylactic acid resin, poly (4-hydroxybutyrate), the compatibilizer obtained in Example 2, the filler, the anti-hydrolysis agent obtained in Example 5, the antioxidant, the plasticizer and the nucleating agent were added to the reaction kettle and stirred for 7 minutes, and then transferred to a twin-screw extruder to extrude the material strips at 195° C. and granulated to obtain a composite material for 3D printing.
[0087] Example 9
[0088] A composite material for 3D printing, comprising the following raw materials in parts by weight: 70 parts of polylactic acid resin, 40 parts of poly(4-hydroxybutyrate) (see the paper "Study on Toughening and Modifying Polylactic Acid and 3D Printing Performance Using Bio-based Degradable Poly(4-hydroxybutyrate)"), 8 parts of a compatibilizer, 12 parts of a filler, 1.5 parts of an anti-hydrolysis agent, 0.8 parts of an antioxidant, 3 parts of a plasticizer, and 3 parts of a nucleating agent;
[0089] The filler is a mixture of nano silicon dioxide and nano antimony trioxide in a mass ratio of 2:1; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the plasticizer is acetyl tributyl citrate; and the nucleating agent is polylactic acid nucleating agent TMC-328;
[0090] The preparation of the composite material for 3D printing comprises the following steps:
[0091] Polylactic acid resin, poly (4-hydroxybutyrate), the compatibilizer obtained in Example 3, the filler, the anti-hydrolysis agent obtained in Example 6, the antioxidant, the plasticizer and the nucleating agent were added to a reaction kettle and stirred for 10 minutes, and then transferred to a twin-screw extruder to extrude material strips at 210° C. and granulated to obtain a composite material for 3D printing.
[0092] Comparative Example 1
[0093] This comparative example is a commercially available common polylactic acid composite material for 3D printing.
[0094] Comparative Example 2
[0095] Compared with Example 9, the compatibilizer was replaced with P4HB-g-GMA obtained by melt grafting of glycidyl methacrylate and poly (4-hydroxybutyrate) (see the paper "Study on Toughening and Modified Polylactic Acid and 3D Printing Performance Using Bio-based Degradable Poly (4-hydroxybutyrate)"), and the rest was exactly the same as Example 9 to obtain a composite material for 3D printing.
[0096] Comparative Example 3
[0097] Compared with Example 9, the anti-hydrolysis agent was replaced with polytriethyl-1,3-phenylcarbodiimide (see the paper "Synthesis and Hygrothermal Aging Research of Polymer Grade Carbodiimide" for details), and the rest was exactly the same as Example 9 to obtain a composite material for 3D printing.
[0098] The composite material for 3D printing disclosed in the present invention is further tested for its effects, and the test results are as follows.
[0099] In order to test the composite material for 3D printing disclosed in the present invention, the tensile strength was measured according to GB / T1040.1-2008 "Determination of tensile properties of plastics"; the Vicat softening temperature was tested using the A50 method according to GB / T 9352-2008; the limiting oxygen index was measured according to GB / T2406.1-2008 "Determination of combustion behavior of plastics by oxygen index method", and the results are recorded in Table 1;
[0100] The hydrolysis method in Table 1 is: the materials obtained in Examples 7-9 and Comparative Examples 1-3 are placed at 60°C for hydrolysis for 48 hours, and the change rate of tensile strength is measured according to the GB / T1040.1-2008 method, and the results are recorded in Table 1;
[0101] Table 1:
[0102]
[0103] According to the data in Table 1, compared with Example 1, it can be seen that the composite material for 3D printing prepared by the present invention has good mechanical properties, heat resistance, hydrolysis resistance and flame retardancy compared with the commercially available common polylactic acid composite material for 3D printing. Compared with Comparative Example 2, Example 9 uses a synthetic compatibilizer and introduces a polysiloxane chain to improve the heat resistance of the material; compared with Comparative Example 3, Example 9 uses a synthetic anti-hydrolysis agent and introduces a polyphosphoramide structure to improve the flame retardancy of the material.
[0104] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A composite material for 3D printing, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of polylactic acid resin, 30-40 parts of poly (4-hydroxybutyrate), 6-8 parts of a compatibilizer, 8-12 parts of a filler, 1.2-1.5 parts of an anti-hydrolysis agent, 0.6-0.8 parts of an antioxidant, 1-3 parts of a plasticizer and 1-3 parts of a nucleating agent; The preparation of the compatibilizer comprises the following steps: Step A1: 4-nitroamphetamine, potassium carbonate and dimethyl sulfoxide are added into a flask to obtain a mixed solution a, and then methacryloyl chloride is added into dimethyl sulfoxide to obtain a mixed solution b. The mixed solution b is slowly added dropwise into the mixed solution a in an ice-water bath at 0° C. After the addition is completed, the temperature is raised to 40° C. and the mixture is stirred at a constant temperature for 10 hours to obtain a reaction product 1; Step A2: Add toluene, hydrogenated silicone oil, hydroquinone, and cis-dichlorobis(pyridyl)platinum into a flask, stir and introduce nitrogen protection, slowly add reaction product 1, slowly raise the temperature to 70-80° C., stir and react for 3-4 hours, and vacuum to remove the solvent to obtain reaction product 2; Step A3: Add the reaction product 2 and toluene into a three-necked flask, heat to 45-55° C., start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5 hours to obtain an aromatic primary amine product; add glycidyl methacrylate, the aromatic primary amine product, toluene and tetrabutylammonium bromide into the flask, start stirring, and stir and react at 40-50° C. for 3 hours to obtain a reaction product 3; Step A4: epichlorohydrin and the reaction product 3 are added to methanol, trimethylamine is added under stirring, and the mixture is refluxed and stirred at 70-80° C. for 3-4 hours to obtain a ring-opening product; the ring-opening product is then added to a sodium hydroxide solution, and stirred at room temperature for 5 hours, and extracted and distilled to obtain a reaction product 4; Step A5: first add poly (4-hydroxybutyrate) to an internal mixer and stir at 60 r / min for 3 min, then add di (tert-butyldioxyisopropyl) benzene, continue stirring for 10-20 min, then add reaction product 4 and stir for 10-20 min, then heat to 155-165° C., mix and stir for 10-15 min, and dry in an oven at 45° C. to obtain a compatibilizer; The preparation of the anti-hydrolysis agent comprises the following steps: Step B1: add bis(4-nitrobenzyl)chlorophosphate to toluene, then add ethyl 2-methyl-3-(methylamino)propionate, stir at 0-5°C for 2h, then heat to 40-50°C, reflux at constant temperature and stir for 1h, filter, extract and dry to obtain reaction product a; Step B2: Add the reaction product a and ethyl acetate into a three-necked flask, heat to 45-55°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5h to obtain the reaction product b; Step B3: Add xylene to a four-necked flask, introduce nitrogen, add the reaction product b and triphosgene at 75°C, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain a diisocyanate product; add the diisocyanate product to the flask, then add 3-methyl-1-phenyl-2-phosphopentene-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; In step B1, the ratio of bis(4-nitrobenzyl)chlorophosphate, toluene, and ethyl 2-methyl-3-(methylamino)propionate is 0.1 mol:80-90 mL:0.1 mol; in step B2, the ratio of reaction product a, ethyl acetate, and sodium dithionite is 0.1 mol:100-110 mL:0.2-0.25 mol; In step B3, the usage ratio of xylene, reaction product b and triphosgene is 100 mL: 0.1 mol: 0.1 mol; the usage ratio of diisocyanate product and 3-methyl-1-phenyl-2-phosphopentene-1-oxide is 0.1 mol: 0.0020-0.0025 mol.
2. A composite material for 3D printing according to claim 1, characterized in that: In step A1, the usage ratio of 4-nitroamphetamine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 45-55 mL; the usage ratio of methacryloyl chloride and dimethyl sulfoxide is 0.1 mol: 25-35 mL; and the usage ratio of mixed solution a and mixed solution b is 50-60 mL: 30-40 mL.
3. The composite material for 3D printing according to claim 1, characterized in that: In step A2, the amount ratio of reaction product 1, toluene, hydrogen-containing silicone oil, hydroquinone and cis-dichlorobis(pyridyl)platinum is 1-1.5 mol: 100-110 ml: 1 mol: 0.5 mol: 0.015-0.020 mol.
4. The composite material for 3D printing according to claim 1, characterized in that: In step A3, the usage ratio of reaction product 2, toluene and sodium dithionite is 0.1 mol: 115-125 mL: 0.1-0.15 mol; the usage ratio of glycidyl methacrylate, aromatic primary amine product, toluene and tetrabutylammonium bromide is 0.35-0.40 mol: 0.1 mol: 360-380 mL: 0.025-0.030 mol.
5. The composite material for 3D printing according to claim 1, characterized in that: In step A4, the amount ratio of epichlorohydrin, reaction product 3, methanol and trimethylamine is 0.2 mol: 0.1 mol: 160-170 mL: 0.01-0.015 mol; the amount ratio of the ring-opening product and the sodium hydroxide solution is 3-4 g: 10 mL, and the mass fraction of the sodium hydroxide solution is 10%; in step A5, the amount ratio of poly (4-hydroxybutyrate), di (tert-butyldioxyisopropyl) benzene and reaction product 4 is 10 g: 0.1 g: 1 g.
6. The composite material for 3D printing according to claim 1, characterized in that: The filler is prepared by mixing nano silicon dioxide and nano antimony trioxide in a mass ratio of 2:1; the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the plasticizer is acetyl tributyl citrate; and the nucleating agent is polylactic acid nucleating agent TMC-328.
7. The method for preparing a composite material for 3D printing according to claim 1, characterized in that: The steps include: Add polylactic acid resin, poly (4-hydroxybutyrate), compatibilizer, filler, anti-hydrolysis agent, antioxidant, plasticizer and nucleating agent into a reactor and stir and mix for 5-10 minutes, then transfer to a twin-screw extruder to extrude material strips at 180-210°C and granulate to obtain a composite material for 3D printing.
Citation Information
Patent Citations
Heat-proof polylactic acid blend and preparation method thereof
CN101157793A
Method for preparing glass fiber-reinforced flame-retardant heat-resistant polylactic acid composite material
CN101798448A